A-transform of Wavelet Frames - Shah, F. A.; Sheikh, N. A. (Communications in Mathematics and Applications, 2012)
In this paper, we introduced the concept of A-transform A = (a_p,q,j,k) and study the action of A on fL^2(R^+) and on its wavelet coefficients. Further, we also establish the Parseval frame condition for A-transform of f L^2(R^+) whose wavelet series expansion is known.